The Effectiveness Of Students' Learning Motivation On Learning Outcomes Using The Reciprocal Teaching Learning Model - Affiana Muthik; Arif Muchyidin; Alif Ringga Persada (Journal of General Education and Humanities, 2022)
The purpose of this study was to see the effectiveness of students' learning motivation on learning outcomes using the reciprocal teaching-learning model. The method used in this research is quantitative. In this study, the instruments used are questionnaires and tests, where the independent and dependent variables will use a questionnaire, and learning outcomes will be measured using tests. At the same time, the test is used to determine whether there is a difference in scores before and after using the mathematical learning model and to determine students' learning outcomes. Based on the objectives of the research and discussion that have been adjusted in previous chapters regarding the effectiveness of the application of the reciprocal teaching-learning model on the learning motivation of students in class VIII in one of the MTs in Tegal, the following conclusions are obtained: student motivation in learning by using the model reciprocal teaching-learning on students' learning motivation. The students' motivation to learn mathematics in class VIII C received an average score of 74.84% for all indicators in the good category. On the learning outcomes of students in the experimental class, namely class VIII C, which at the time of learning using the reciprocal teaching-learning model, the average value of the class was 82.22. While in the control class, namely class VIII D, which uses conventional methods at the time of learning, the average score is 69.13. This shows that using reciprocal teaching-learning models can motivate students to learn and ultimately lead to improved learning outcomes.